2020
DOI: 10.21608/ejabf.2020.73595
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological quality of groundwater in the Saïs plain (Morocco)

Abstract: Keywords:Saïs plain, Groundwater Microbiology contamination MoroccoThe groundwater of Saïs plain is the main drinking-water supply of Fez-Meknes region (Saïs basin) in Morocco. A large number of people living in this region depend on groundwater drawn from open dug wells for their daily water requirements. The main purpose of this study is to identify the major factors affecting groundwater quality by means an analysis of the microbial composition. The quality of 144 groundwater wells is evaluated in the Saïs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…-Water sources near septic tanks and latrines, landfill of sewage sludge in the ground. These causes are similar to those found in the studies conducted by El Haissouffi et al [8] on groundwater pollution in Fez and on the Physico-chemical and bacteriological quality of groundwater in sais plain [9].…”
Section: Bacteriological Water Qualitysupporting
confidence: 90%
“…-Water sources near septic tanks and latrines, landfill of sewage sludge in the ground. These causes are similar to those found in the studies conducted by El Haissouffi et al [8] on groundwater pollution in Fez and on the Physico-chemical and bacteriological quality of groundwater in sais plain [9].…”
Section: Bacteriological Water Qualitysupporting
confidence: 90%
“…Most of the research work on Salmonella in the environment has been carried out in water environments, such as wells (Lotfi et al, 2020, Nassri et al, 2021, running waterways (Ben Moussa et al, 2014), water from dams (Chahboune et al, 2014), wastewaters (Ait Melloul and Hassani, 1999), and seawater (Setti et al, 2009). However, the complete study by serotyping and the study of antibiotic resistance is generally not carried out or not reported.…”
Section: Occurrence Of Salmonella In the Environmentmentioning
confidence: 99%
“…and cutaneous larva migrans caused by Ancylostoma spp. These parasitic zoonoses are associated with the presence of animals, mainly dogs and cats, in places where humans can be infected, such as squares and public parks (Despommier, 2003;Hotez & Wilkins, 2009;Rybinsk-Elefant et al, 2010;Lotfi et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%